Evaluation of Antileishmanial Activity of Osteospermum ecklonis Extract of Aerial Parts against Leishmania donovani: in vitro(Conference Paper) # - Jewely, Hind Mohammed; Thukaa Zuhair (Iraqi Journal of Pharmaceutical Sciences, 2023)
Abstract Lack of safe available non-resistant treatment for visceral leishmaniasis (Kala-azar) keeps limiting the complete cure of this disease ,drugs that have toxic side effects or lack of effectiveness have led to disease relapse ,all these factors have lightened the way to the search for imperative drugs from natural resources that have been shown to have antileishmanial activity through literature survey. In the present study, the comparative in vitro anti-leishmania activity of various fractions of Osteospermum ecklonis aerial parts fractions have been evaluated. Extracts were prepared through maceration and Soxhlet apparatus using 85% methanol and fractionation was done by separating the active constituents according to the differences in their polarities using petroleum ether and n-butanol respectively. The resultant fractions( petroleum ether as well as n-butanol fractions )were chosen for effective inhibition of Leishmania donovani, The results prove with no doubt that the petroleum ether fraction of the maceration aerial parts in a concentration of 2.5 mg/ml had better antileishmanial activity than other concentrations of tested samples and the result coincided with the anti-leishmaniasis activity of official treatment (pentostam®) ,This finding can be attributed to the terpene nature of the materials used to be existed in such fraction. This observation have paved the road to step in for extended studies in relation to the conventional herbal medicines for better and safe alternatives to available synthetic chemical drugs.